Design and Development of Leg-Wheel Hybrid Hexapod along with Machine Learning Algorithm implementation - Harikrishnan Madhusudanan (Institute of Advanced Engineering and Science, 2015)
The conventional mobile robotic platforms which either uses wheels or legs are quite familiar and each one of them has its own advantages and disadvantages. The wheeled robot is suitable for only plain and smooth terrain, whereas the legged robot can travel in any kind of terrain but is comparatively slower than the wheeled robot. So, a hybrid of both wheeled and legged platform would be quite suitable for any kind of terrain. The primary focus of this paper is to design and develop a leg-wheel hybrid robotic platform with a concurrent engineering and mechatronics approach to produce results with optimised design metrics at each and every stage of its development. An overall view of the entire mechatronics system is considered for design and development of the robot at each and every stage rather than a sequential engineering approach.